The Moderation Effect of Competitive Strategy on The Relationship Between Debt Levels and Firm Performance - Dhia Shofiah Mardiana (Jurnal Akuntansi dan Pajak, 2023)
Among the most important factors in achieving sustainable performance is the determination of capital structure. An optimal capital structure strikes a balance between risk and return received so as to improve firm performance. The purpose of this study was to examine and analyze the effect of debt level on firm performance with competitive strategy as the moderator. This study focused on businesses that were listed on the Indonesia Stock Exchange between 2015 and 2019. 62 companies were chosen as samples using the purposive sampling method, yielding 277 observations. Multiple regression analysis and moderated regression analysis were used to analyze the data. This study found that debt level has a negative effect on firm performance, and that competitive strategy moderates the influence of debt level on firm performance.